Ambrosia artemisiifolia control in agricultural areas: effect of grassland seeding and herbivory by the exotic leaf beetle Ophraella communa - Cardarelli, Elisa; Musacchio, Arianna; Montagnani, Chiara; Bogliani, Giuseppe; Citterio, Sandra; Gentili, Rodolfo (NeoBiota, 2018)
Ambrosiaartemisiifolia (common ragweed) is an invasive species native to North America and was accidentally introduced to Europe in the 19 th century. Widespread in disturbed habitats, it is a major weed in spring-sown crops and it causes serious allergic rhinitis and asthma due to its allergenic pollen. The aim of this research was to analyse the effects of both competitive vegetation and herbivory by Ophraellacommuna to control A.artemisiifolia in an agricultural area of north-western Italy. Hayseed mixtures, both over-seeded over the resident plant community or after ploughing, when seeded before the winter season, were able to suppress the establishment of A.artemisiifolia as well as to reduce its growth in terms of plant height and inflorescence size. Defoliation of A.artemisiifolia by O.communa at the end of the growing season was conspicuous but most of the plants still produced flowers and seeds. However, significant O.communa attack was recorded for reproductive structures. As for non-target species, O.communa was mainly recorded on Asteraceae, with low density and low degree of damage. Reduction of inflorescence size due to competitive vegetation and damage to male flowers by O.communa may diminish the amount of available pollen. The results of this study may be useful for the implementation of management measures to control A.artemisiifolia in agricultural areas using mixtures of native species.